PERAN NABI DALAM PROSES PEWAHYUAN ; Studi Kitab al-Naba’u al-'Azim Karya Muhammad ‘Abdullah Darraz - Zarkasyi, Ahmad; Lestari, Lenni (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2018)
?Alquran is like a diamond shining over all the surface?. That is well-known quote from Muhammad Abdullah Darraz in illustrating Alquran. From that statement, it is able to be summarized that he had provided a new paradigm of Alquran through his work, Al-Naba?u Al-?Azim, Nazratun Jadidah fi Alquran. This paper will focus on several views in his book including the meaning of Alquran, hadis al-qudsi, hadis al-nabawi, wahyu al-nash, wahyu al-ma?na, ta?lim bi al-Ibtida?I, and ta?lim bi al-Iqrar or naskh Intiha?i. Furthermore, this paper will analyze the theory of hadis al-qudsi I hadis al-nabawi and the consequences of classifiying Alquran, Hadis al-Qudsi, and Hadis al-Nabawi, including the role of the prophet in revelation methode. Based on Darraz?s view, Alquran is not able to be defined. The definition of Alquran which has been commonly known is only the efforts of traditional muslim scholars to approach the essential charachters of Alquran. The clearest differences among Alquran, hadis al-qudsi, and hadis al-nabawi are possible to be seen from three aspects. Those are, the way of revelation imparting (wahyu al-nash and wahyu al-ma?na), textual indication (nash syar?i), and revelation purpose (ta?abbud bi tilawatih and tahaddi (challenging). The principal philosophy of differentiating among Alquran, hadis al-qudsi, hadis al-nabawi is abridging the human to perform the religious obligation. The role of prophet Muhammad in revelation process is simply passive.